The impact of using the digital story strategy in the achievement of the history subject for the sixth grade students in Jordan - Almherat, Rasha Mohammed; Shehadeh, Fawaz Hassan (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed the effect of using the digital story strategy in the achievement of the history subject for the sixth grade students in Jordan. The study used the semi-experimental method and the achievement test was prepared after verifying its validity and stability, the sample of the study consisted of (44) sixth grade male and female student. The study sample was divided into two experimental groups, the first group consisting of (22) student who were taught using the digital story strategy, and the other group consisted of (22) students who were taught in the usual way, the results showed statically significant differences between the average performance of the two groups for the experimental group, as a result, the study recommended that the teachers of history should be trained to use the digital strategy.